Social Media Marketing A Strategic Approach - Debra Zahay; Roberts, Mary Lou; Parker, Janna M.; Barker, Melissa S.; Barker, Donald (Cengage, 2023)
Teach students how to use social media to market effectively with the latest developments, social media initiatives and best practices found in Zahay/Roberts/Parker/Barker/Barker's popular 'Social media marketing: a strategic approach'. Updated content highlights both emerging and established marketing techniques within popular social media platforms. Strong conceptual frameworks are punctuated with recent examples and practical cases. Expanded coverage of consumer behavior guides students in identifying with virtual communities, mastering visual storytelling and maximizing content marketing. New chapters address managing a digital marketing organization and leveraging paid advertising and social media influencers. A step-by-step planning model leads students through branding strategies and an organization's integrated marketing communication approach while creating an actual social media marketing plan. Students also gain insights for create their own strong personal brand.